Characterization of Plasma Carnitine Level in Obese Adolescent Korean Women - Yoo, Hye Hyun; Yoon, Ho Joo; Shin, Hye Jung; Lee, Sang Hyup; Yoon, Hye-Ran (KOREAN SOC APPLIED PHARMACOLOGY, 2009)
Carnitine is known to be involved in lipid metabolism and affects body composition as well as energy metabolism of the whole body. Improvement of obesity by L-carnitine supplement suggests that obesity can be related with the abnormality of carnitine metabolism and therefore, plasma carnitine level in normal and obesity groups was investigated. For the characterization of plasma carnitine level in obese people, 60 plasma samples collected from Korean women subjects were analyzed using LC/MS and plasma fatty acid level was also determined using GC/MS. Additionally, several clinical chemical parameters including fasting glucose, cholesterol, AST, and ALT level were measured. All the data obtained were combined and pattern recognition analysis was carried out with the dataset. Obese group showed a different metabolic pattern compared with normal group. Plasma acylcarnitine level of the obese group was found to be 11.7 mu g/ml, which was higher than that of normal group (8.0 mu g/ml). Statistically significant differences in plasma fatty acid level were not observed between the two groups. Other clinical parameters for the obese group were within normal ranges but AST and ALT levels were slightly elevated compared to normal group. The obese group showed elevated plasma acylcarnitine level.
Keywords: ADRIAMYCIN-TREATED RATS; FATTY-ACID-METABOLISM; WEIGHT-LOSS; DEFICIENCY; LIVER; MICE; PALMITOYLTRANSFERASE-1; MITOCHONDRIAL; PROFILES; SYSTEM